Integridade ambiental de bacias hidrográficas submetidas a diferentes graus de conservação - Gatzke, Estevão Gottlieb (2017)
The present study evaluated the environmental integrity of two streams in the city of Londrina-PR, a typical urban (Cambé) and a rural one (Taquara). Correlations among variables were analyzed: (i) abiotic, (ii) related to the structure of benthic macroinvertebrate assemblies and (iii) associated to land use and occupation. In addition, environmental integrity indexes associated with macroinvertebrate assemblies were also applied. It was tested the hypothesis that the rural stream presents greater environmental integrity than the urban stream. The analyzed abiotic variables were water temperature, pH, dissolved oxygen, total dissolved solids, electrical conductivity and turbidity. The structure of the assemblies was evaluated from the abundance of individuals and the richness, equitability, dominance and diversity of families. Concerning the use and occupation of the soil, the relative areas related to the vegetal cover, agriculture, exposed soil, impermeabilation and water body were evaluated. Regarding the environmental integrity analysis, the PAR (Rapid Environmental Parameters), BMWP (Biological Monitoring Working Party), ASPT (Average Score Per Taxon) and percentage of Chironomidae and EPT (Ephemeroptera, Trichoptera and Plecoptera) were analyzed. The macroinvertebrates were used as bioindicators, being collected with the equipment "kick net" type, in April, May, June, August and September of 2016, when measurements of width, depth and extension of riparian vegetation were also estimated. The fauna composition and the Spearman correlation between the abiotic variables and the structure parameters of the assemblies were analyzed. Jaccard's similarity analysis was applied between the points, based on abundance and family richness, and canonical correlation analysis (CCA) to evaluate the relative contribution of the studied variables to the differentiation among the basin points. The total number of individuals sampled was 4171, distributed in 40 taxa. In Cambé, 3053 macroinvertebrates were collected, corresponding to 30 families, while in Taquara there were 1118 macroinvertebrates, identified in 25 families. In both streams a tendency of improvement of environmental integrity along the longitudinal gradient was observed. The CCA revealed that Cambé is characterized by impermeable urban areas and exposed soil. This characteristic was shown to be associated with an increase in the concentration of total dissolved solids, electrical conductivity and water temperature. The removal of the riparian vegetation and the consequent displacement of sediment to the main channel tends to intensify the surface runoff of the rainwater. These physical and chemical structures had a direct impact on the structure of the macroinvertebrate assemblages, raising the dominance of a tolerant group and reducing the richness, equitability and diversity of families. Taquara presented itself in a less critical environmental situation than Cambé, being characterized as altered. In the studied section, agricultural areas predominate followed by fragments of secondary forests, associated with larger extensions of riparian vegetation. This configuration tends to reduce the surface runoff from the margins and, thus, reduce sediment entry, reflecting lower concentrations of dissolved solids, electrical conductivity and water temperature. The greater protection of the entrance of allochthonous sediments tends to increase the stability of the substrate, increasing its colonization potential, as demonstrated by the higher values of richness, equitability, diversity, PAR, BMWP, ASPT and EPT presented by this stream. The results indicate that the two streams are impacted, the Cambé to a greater degree due to the urban interferences, and the Taquara with less degree of degradation, but still submitted to environmental stress coming from the agriculture.